Aktivitas Anti Inflamasi Ekstrak Biji Litsea Garciae Vidal Pada Odema Telapak Kaki Dan Gambaran Histologis Kaki Mencit - Mustika Sari; Henny Sulistiany (Research Center for Biology-Indonesian Institute of Sciences, 2021)
Litsea garciae or malek is a native species from Borneo and belongs to the Lauraceae family. Scientifically, the use of these plants is not widely known. The purpose of this study was to determine the anti-inflammatory activity of Litsea garciae seeds against edema in mice feet and to determine the histology of the carrageenan-induced integument thickness of mice. The study used a completely randomized design with 5 treatment groups. The treatment group consisted of a negative treatment group (K1), a positive treatment group (K2) with 3 different dosages of Malek seed extract groups. The treatment doses used were Malek seed extract at a dose of 0.625 mg/g BW (P1), 1.25 mg/g BW (2), and 2.50 mg/g BW (P3). Edema percentage and integument thickness were analyzed by the One-Way ANOVA test with (α = 0.05). The results showed that the Malek seed extract dose of 0.625 mg/g BW had anti-inflammatory activity against edema of the mice's feet. The percentage of inflammation with doses of 0.625 mg/g BW, 1.25 mg/g BW and 2.5 mg/g BW was 31.10%, 22.58%, and 25.83%. The percentage of reduction in inflammation in the positive control treatment of Na-diclofenac (42.70%) was significantly differ-ent from the treatment of Malek seed extract at a dose of 0.0625–2.5 mg/g BW. The percentage of reduction in inflammation in the group treated with 1.25 mg/g BW (P2) Malek seed extract was not significantly different from the 2.5 mg/g BW (P3) treatment of Malek seed extract. The results of histological observations of mice's feet showed that the extract of Malek seeds did not have a significant effect on the thickness of the carrageenan-induced mice leg integument.